Implementation of Guided Inquiry Learning Model In Improving Critical Thinking Abilities of Grade VI Students - Yohana Panjaitan; Natalina Purba; Jon Roi Tua Purba (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
This study aims to Implement the Guided Inquiry Learning Model in Improving Critical Thinking Skills of Grade VI Students at UPTD Sd Negeri 125138 Pematangsiantar. This research is a qualitative research. Based on the results of research that has been done through observation, interviews, and documentation, it can be concluded that the implementation of the guided inquiry learning model in the subject of PPKn, especially on the material "Norms, Rights, and Obligations", has a positive influence on the development of critical thinking skills of grade VI students of UPTD SD Negeri 125138 Pematangsiantar. First, from the aspect of learning implementation, the guided inquiry model is able to present a more active and participatory learning atmosphere. Second, from the results of the analysis of critical thinking skills, it is known that the majority of students (61.3%) have demonstrated good critical thinking skills. Students in this category have been able to identify problems, convey arguments logically, and draw conclusions appropriately. Third, the results of the evaluation based on the CIPP model show that the context of the application of the guided inquiry model is very relevant to the needs of students in practicing higher-order thinking skills. Thus, it can be concluded that the guided inquiry learning model is effective for use in PPKn learning to develop students' critical thinking skills, but supporting strategies are needed to address differences in student characteristics and levels of participation.